Pengaruh Penggunaan Digital Payment dan Service Quality terhadap Perilaku Konsumtif Masyarakat dengan Consumer Trust sebagai Variabel Mediasi dalam Perspektif Islam - Fitri Salsabila; Vitria Susanti; Liya Ermawati (Journal of Islamic Economics and Finance, 2024)
In Indonesia, the use of digital payments is increasingly widespread, especially among the younger generation. Along with the increasing use of digital payments, it has also made people in Indonesia become more consumptive. It is important to understand the factors that influence consumer behavior in using these services. This research aims to analyze the influence of the use of digital payments and service quality on the consumer behavior of the people of Bandar Lampung, by considering the role of consumer trust as a mediating variable. This research uses descriptive research methods with a quantitative approach. The research population is people who live in Bandar Lampung City, while the sample consists of 96 respondents. The sampling technique uses non-probability sampling with a sampling technique, namely the purpose sampling technique. The data analysis method uses Partial Least Square (PLS) and then the data obtained is processed using SmartPLS 4 software. The research results show that there is an insignificant negative influence between digital payment variables on consumer behavior. There is a positive and significant influence between digital payment variables on consumer trust. There is an insignificant positive influence between service quality and consumer behavior. There is a positive and significant influence between service quality and consumer trust. There is an insignificant positive influence between the consumer trust variable on consumer behavior. Trust does not mediate the relationship between digital payments and service quality on consumer behavior.